Thirty years of cornea cultivation: long‐term experience in a single eye bank. (2nd August 2012) - Linke, Stephan J.; Eddy, Mau‐Thek; Bednarz, Jürgen; Fricke, Otto H.; Wulff, Birgit; Schröder, Ann‐Sophie; Hassenstein, Andrea; Klemm, Maren; Püschel, Klaus; Richard, Gisbert; Hellwinkel, Olaf J. C.
Abstract. Purpose: To evaluate donor demographics, trends in donor tissue procurement and tissue storage over a long period. Methods: A retrospective, longitudinal, descriptive analysis was undertaken of data from the Hamburg Eye Bank Data Base (HEB‐DB) that had been collected between 1981 and 2010. Data on 54 parameters of cornea donors [including clinical history, age, death cause, gender and death‐to‐explantation interval (DEI)] and of cultivated corneas (endothelial quality and development in culture, cultivation period, microbiological contamination) were retrieved. These data were analysed statistically, focusing on the historical development of the eye bank. Results: At the time of retrieval (June 2010), the HEB‐DB contained data on 10 943 corneas (5503 donors). Most donors were men (65%) and had died from cardiopulmonary (n = 801)/cerebral (n = 261) failure or as the result of a polytraumatic accident/suicide (n = 602). Within these years, donor age, DEI and storage time increased. The percentage of stored corneas suitable for transplantation displayed a variable but increasing trend; in 2007, almost 75% of the stored corneas were transplanted. Between 1995 and June 2010, the median microbiological contamination rate was 5.3%. A change in the procurement procedure from enucleation to corneoscleral explantation in 2008 led to a briefly increased contamination rate. Conclusion: Donor demographic data run parallel to the general demographic development. Our analysis indicates a dynamic development of the eye bank over the last 30 years and emphasizes the need for an active quality management in coping with the challenges of modern eye banking.